Prevalence of pregnancy-related pelvic girdle pain and associated factors in Australia: a cross-sectional study protocol. Issue 11 (15th November 2017) - Ceprnja, Dragana; Chipchase, Lucinda; Gupta, Amitabh
Abstract : Introduction: Pregnancy-related pelvic girdle pain (PPGP) is a common musculoskeletal disorder. Women with PPGP report difficulty performing everyday functional activities, such as standing and walking. However, the magnitude of the problem remains unknown in Australia. It is important to determine how many women are affected by this condition and the factors associated with PPGP as this will direct healthcare services to being able to better manage women during pregnancy. Thus, this study aims to determine the prevalence of PPGP and associated factors in a Western Sydney population. Methods and analysis: This study is a cross-sectional study to be conducted at a single hospital in Australia. Participants will be over 18 years of age, between 14 and 38 weeks gestation and recruited randomly from all pregnant women attending antenatal care. Participants will have anthropomorphic measures recorded, such as height and body weight, and be asked to complete questionnaires about their current pregnancy, sociodemographic information, ethnoculture, occupational factors and participation in functional activities. The classification of PPGP will be made as per the published guidelines and will include a physical examination. Ethics and dissemination: Ethical approval has been granted by the Human Research Ethics Committees of Westmead Hospital, Sydney, and Western Sydney University, Sydney. Dissemination of results will be via journal articles and conference presentations. Trial registration number: ACTRN12617000904370 .